Semantics - Saeed, John I. (Chichester, West Sussex [England] John Wiley & Sons, Inc., 2016)
"Revised and updated to reflect recent theoretical developments in the field, Semantics, 4th Edition, presents an engaging and accessible introduction to the study of meaning in language for students new to the field of semantics. Covers all of the basic concepts and methods of the field of semantics, as well as some of the most important contemporary lines of research Features a series of new exercises, along with their solutions, that are arranged by level of difficulty Addresses componential theory, formal semantics, and cognitive semantics, the three main current theoretical approaches to semantics Includes revisions and updates that reflect the most recent theoretical developments"--Provided by publisher.
"Covers all of the basic concepts and methods of the field of semantics, as well as some of the most important contemporary lines of research"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Semantics